THE EVALUATION IMPACT OF THE CLEAN WATER ASSISTANCE PROGRAM IN PUSER VILLAGE, TIRTAYASA DISTRICT, SERANG : Cynthia Agatha, Rahmawati - Cynthia Agatha; Rahmawati (LPPM STIA Banten, 2023)
The government's efforts to support SDGs on access to clean water services, the Serang district government held a clean water assistance program in Puser Village. The clean water assistance program in Puser Village has three clean water assistance programs namely, Governor Assistance, PAMSIMAS and DAK. Even though there have been three program assistance from the Settlement Office, there are still many people in Puser Village who use irrigation water for their daily needs. This study aims to determine the impact of the clean water assistance program in Puser Village. Researchers use the theory of impact evaluation from Samoedra Wibawa with four indicators, namely the impact on individuals, the impact on society, the impact on organizations and the impact on social systems. The method used in this research is descriptive qualitative research method. Primary data was obtained through observation and structured interviews with informants, namely the Puser Village community, the Village Government and the Serang Regency Settlement Office Government who were involved in managing the Clean Water Assistance Program. The results of the research on the evaluation of the clean water assistance program in Puser Village showed results that had little impact. This is due to the lack of community participation in using the clean water assistance program, as well as the lack of performance of KP-SPAM in tackling repairs to water towers which are one of the obstacles for the community to use the clean water program. The Government of the Serang Regency Settlement Service also acknowledged that the lack of assistance to the community hampered the process of changing the hygienic behavior of the people in Puser Village. Keywords; Evaluation, Water, Puser Village